Mechanisms and thresholds of land use affecting surface water quality in Hangzhou City’s residential areas - Qianhu Chen; Jinye Huang (Ecological Indicators)
Examining the relationship between land use and surface water quality in different residential areas is essential for enhancing the overall quality of the human environment and for making sustainable land use policies. In the center of Hangzhou, eleven land use metrics were measured to indicate land use function, utilization intensity, and spatial structure characteristics among three residential types: multi-story, small high-rise, and high-rise, which were selected as research samples. Six water quality indicators were collected from monitoring stations during 2023. We employed correlation analysis to examine the inherent connections between land use metrics and surface water quality. On the basis of nonlinear regression models, including power, exponential, and cubic, one-on-one relations between land use metrics and water quality indicators were fitted. The conclusions are as follows: (1) Surface water pollution varied among different types of residential areas, with NH3-N and TP being the most significantly impacted indicators of water quality. (2) The development of set density and fragmentation of green space were the major reasons for the increase in pollutant concentration. However, we can successfully control this negative impact by increasing the degree of green space dominance and aggregation. (3) To meet the standards for Class III water quality, various types of residential areas must adopt distinct control indicator thresholds: Compared to multi-story residential areas’ dispersed green spaces, small high-rise residential areas feature highly interconnected and clustered green spaces, which increases surface runoff pooling and spillover. Green spaces per unit area must perform environmental purification in high-rise residential areas due to their higher population density, which puts more demands on their design and ecological service activities. Thus, multi-story and high-rise residential areas should raise their minimum green area ratio by 3.2% and 2%, respectively, while small high-rise residential areas should remain unaltered. Meanwhile, the maximum unit density of the three types of residential areas should be limited to 135 units/ha, 196 units/ha, and 190 units/ha to manage development intensity and decrease pollution.